Petőfi napja, Kossuth éve, avagy ki és hogyan csinálja a történelmet? - Miru, György (Studia Litteraria, 2024)
This paper examines the role of Petőfi and Kossuth – two important figures in the Hungarian historical memory – in the events of 1848 which was a turning point in history, and it led to changing the existing structures. Moreover, the paper discusses how Petőfi and Kossuth tried to interpret recent historical events and the ways they tried to make the public accept these interpretations.